Tantangan Nasional untuk Menghadapi Globalisasi - Sulistyanto . (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
Humans want to live together help each other, mutual assistance, and mutual respect that is expected with better education, ie the quality of education. Globalization contains various contradictions by John Naisbitt, are: 1) The global culture as opposed to the local culture; 2) Univesal opposite with individual; 3) Traditional opposite to modern; 4) Long-Term opposite to short-term; 5) The competition contrary to the equal opportunities; 6) Limited human intellect opposite to the explosion of science and technology; and 7) Spiritual opposite to material. The idea of ​​